State of polycyclic aromatic hydrocarbon (PAH) contamination in the Saint John Harbour, New Brunswick, Canada. (April 2023) - Diesbourg, Emilie; MacDonald, Morgan; Reid, Heather Bauer; MacKinnon, Roxanne; Reinhart, Bethany; Mercer, Angella; Crémazy, Anne
Abstract: This study examined the concentrations and compositions of polycyclic aromatic hydrocarbon (PAH) contaminants in the surficial sediments of the Saint John Harbour (SJH) and assessed PAH exposure to local aquatic biota. Our findings suggest that sedimentary PAH contamination is heterogeneous and widespread in the SJH, with several sites exceeding the Canadian and NOAA recommended guidelines for the protection of aquatic life. Despite high concentrations of PAHs at some sites, there was no indication that local nekton was affected. Lack of a biological response may be due in part to a low bioavailability of sedimentary PAHs, presence of confounding factors (e.g., trace metals), and/or adaptation of local wildlife to the historic PAH contamination in this region. Overall, although no indication of effects to wildlife was observed with the data collected in the present study, continued efforts should be made to remediate highly contaminated areas and reduce the prevalence of these compounds. Highlights: Mean total sediment PAH concentration exceeded CCME ISQGs in 6/13 sampled sites. There was no significant change in overall sediment PAH concentration (2018–2022). There is no immediate threat of sediment PAH contamination to sampled nekton. There may be limited bioavailability of PAHs, decreasing their exposure to biota.